Glycosylation Pattern and in vitro Bioactivity of Reference Follitropin alfa and Biosimilars - Riccetti, Laura; Sperduti, Samantha; Lazzaretti, Clara; Klett, Danièle; De Pascali, Francesco; Paradiso, Elia; Limoncella, Silvia; Potì, Francesco; Tagliavini, Simonetta; Trenti, Tommaso; Galano, Eugenio; Palmese, Angelo; et al. (Frontiers in Endocrinology, 2019)
Recombinant follicle-stimulating hormone (follitropin alfa) and biosimilar preparations are available for clinical use. They have specific FSH activity and a unique glycosylation profile dependent on source cells. The aim of the study is to compare the originator (reference) follitropin alfa (Gonal-f®)- with biosimilar preparations (Bemfola® and Ovaleap®)-induced cellular responses in vitro. Gonadotropin N-glycosylation profiles were analyzed by ELISA lectin assay, revealing preparation specific-patterns of glycan species (Kruskal-Wallis test; p<0.05, n=6) and by glycotope mapping. Increasing concentrations of Gonal-f® or biosimilar (1x10-3-1x103 ng/ml) were used for treating human primary granulosa lutein cells (hGLC) and FSH receptor (FSHR)-transfected HEK293 cells in vitro. Intracellular cAMP production, Ca2+ increase and β-arrestin 2 recruitment were evaluated by BRET, CREB and ERK1/2 phosphorylation by Western blotting. 12-h gene expression, and 8- and 24-h progesterone and estradiol synthesis were measured by real-time PCR and immunoassay, respectively. We found preparation-specific glycosylation patterns by lectin assay (Kruskal-Wallis test; p<0.001; n=6), and similar cAMP production and β-arrestin 2 recruitment in FSHR-transfected HEK293 cells (cAMP EC50 range=12±0.9–24±1.7 ng/ml; β-arrestin 2 EC50 range=140±14.1– 313±18.7 ng/ml; Kruskal-Wallis test; p≥0.05; n=4). Kinetics analysis revealed that intracellular Ca2+ increased upon cell treatment by 4 μg/ml Gonal-f®, while equal concentrations of biosimilars failed to induced a response (Kruskal-Wallis test; p<0.05; n=3). All preparations induced both 8 h- and 24 h-progesterone and estradiol synthesis in hGLC, while no different EC50s were demonstrated (Kruskal-Wallis test; p>0.05; n=5). Apart from preparation-specific intracellular Ca2+ increases achieved at supra-physiological hormone doses, all compounds induced similar intracellular responses and steroidogenesis, reflecting similar bioactivity and overall structural homogeneity.